AB0953 EAR INVOLVEMENT IN PATIENTS AFFECTED BY JUVENILE IDIOPATHIC ARTHRITIS. (June 2019) - Conti, Giovanni; Barbera, Giulia La; Visalli, Carmela; Alberti, Giuseppe; Pasquale, Paola De; Borgia, Francesco; Ciodaro, Francesco
Abstract : Background: Few clinical studies in pediatric patients have shown a possible link between hearing loss and Juvenile idiopathic arthritis (JIA). It could be related to the involvement of the joints of the ossicular chain as a result of the autoimmune inflammatory process in the middle and inner ear Objectives: The aim of this study was to assess the frequency of hearing impairment in patients affected by JIA versus a healthy control group. Methods: We studied 64 ears of 32 JIA patients (25 girls and 7 boys, mean age 15 years, age range 8-19 years) from June to December 2018. The mean disease duration was 7 years (+/- 4 DS). Polyarticular JIA was diagnosed in 6 patients, oligoarthritis JIA in 19; 5 patients had psoriatic arthritis and 2 spondyloarthritis. The control group consisted of 60 ears of 30 healthy children, sex-and age-matched. Patients with previous otitis media at least 3 months and/or ear surgery were excluded. The study was approved by the local ethics committee and parents and/or patients signed their informed consent. All subjects underwent audiological examination involving otomicroscopy, audiometry, tympanometry and stapedius reflex. Rheumatologic evaluation included joint examination with application of a measure of functional ability (disability) using the Childhood Health Assessment Questionnaire (CHAQ). The investigators were blinded about JIA type, severity, duration, and treatments of the patients. Results: 11/32 (34%) JIA patients had abnormal audiological exam. Hypoacusia was significatively more frequent (p<0, 05) in JIA patients (15/64 ears=23%) respect to the control group. In particular, hypoacusia was associated to psoriasic arthritis (6/15 ears). Conductive hearing loss was detected in 12/15 involved ears, while sensorineural type in 3/15. In the JIA group, according to the Jerger classification for tympanometry, abnormal findings were observed in 7 ears. The stapedius reflexes were absent in only one patient (3%). JIA patients with hypoacusia had a greater CHAQ (0.4+/-0.3) than JIA patients with normal audiometry (0.18+/-0.29). Conclusion: The presence of hearing impairment and/or abnormal tympanogram suggests early involvement of the tympanic-ossicular complex, especially in patients with psoriatic arthritis. These findings could be a marker of the JIA activity. Therefore, it is advisable that JIA patients perform periodic audiological examination to early detect eventual hearing impairment, in order to prevent hearing loss in adult age. References: [1] M.EG Amani: Acta Oto-Laryngolica 2016 [2] A.I.C. Cruz: Reumatologia Clinica 2017 [3] F Borgia: Acta Derm Venerreol 2018 Disclosure of Interests: None declared